2015
DOI: 10.1002/2014jc010448
|View full text |Cite
|
Sign up to set email alerts
|

Baroclinic instability and the mesoscale eddy field around the Lofoten Basin

Abstract: The vigorous mesoscale eddy field around the Lofoten Basin west of northern Norway is thought to be related to eddy shedding from the Norwegian Atlantic Current flowing along the Norwegian coast. Here we study baroclinic instability in the current with a particular focus on the influence of topography. The flow over the steepest part of the continental slope is found to be the most unstable. The growth characteristics cannot be understood from Eady theory alone but require the consideration of interior potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 43 publications
6
71
0
Order By: Relevance
“…This is in line with Benilov [], who showed that bottom depressions stabilize ACEs, which can reduce breakups and reformation of ACEs. The larger eddy generation in the eastern Lofoten Basin near the continental slope and along the northern part of the slope current (above 70°N) is associated with the eddy shedding in these regions from the slope current [ Rossby et al ., ; Isachsen , ; Raj et al ., ]. Indications of ACEs being shed from the Norwegian Atlantic Front Current along the Mohn Ridge can also be seen in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with Benilov [], who showed that bottom depressions stabilize ACEs, which can reduce breakups and reformation of ACEs. The larger eddy generation in the eastern Lofoten Basin near the continental slope and along the northern part of the slope current (above 70°N) is associated with the eddy shedding in these regions from the slope current [ Rossby et al ., ; Isachsen , ; Raj et al ., ]. Indications of ACEs being shed from the Norwegian Atlantic Front Current along the Mohn Ridge can also be seen in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…9) may alter the stability characteristics of the flow leading to enhanced baroclinic instability (Isachsen 2011). The steeper topography associated with these conditions also tends to make the flow more baroclinically unstable (Spall 2010;Isachsen 2015). This in turn will impact the cross-stream eddy fluxes of heat and salt from the NIIC into the interior, which is an important component of the local overturning cell in the Iceland Sea (Våge et al 2011).…”
Section: Pathway Of the Nijmentioning
confidence: 99%
“…Figure a) is significantly reduced downstream of the Lofoten slope. We hypothesize that this reduction may be due, but not limited (reasons to be discussed later), to the vigorous cross‐slope eddy shedding here [ Isachsen , ; Raj et al ., ; Jakobsen et al ., ]. To support this conjecture, the slope‐to‐basin propagation of temperature anomaly is studied.…”
Section: Poleward Propagating Warm Temperature Anomaliesmentioning
confidence: 99%
“…This indicates that mesoscale eddies account for a large fraction of the total EKE. These eddies are shed persistently from the slope current and drift into the LB interior (see the supporting information animation) [ Isachsen , ; Raj et al ., ; Søiland and Rossby , ; Koszalka et al ., ; Rossby et al ., ; Köhl , ].…”
Section: Poleward Propagating Warm Temperature Anomaliesmentioning
confidence: 99%